Pharmacognostical Potential of Capparis deciduas Edgew. - P. D. Verma, R.D. Dangar, K. N. Shah, D. M. Gandhi, B. N. Suhagia (Journal of Applied Pharmaceutical Science)
Capparis decidua (Family, Capparidaceae) is commonly known as ‘Kair’. It is distributed throughout the arid regions of India and other countries. Kair is a caducous plant, so in the foliage condition mainly stem and fruits are common. It is also known as Capparis aphylla. Since the plant is xerophytic, it is generally found in dessert area and is highly draught resistant plant which can survive for long. Tribal people prepare pickle from the fruits of Kair. Some of the communities use Kair fruits as vegetables and food additives. The plant is used traditionally as anti-inflammatory, laxative, anti-diabetic, anthelmintic, antibacterial, astringent, digestive, diaphoretic and anodyne. It is reported to possess beneficial effects in various ailments, like rheumatism, asthma, diabetes, liver disorders, hypercholesterolemia, hypertension and microbial infections. Studies have revealed the presence of various phytoconstituents especially spermidine alkaloids, glucosinolates and other glycosides, β-sitosterol, rutin, l-stachydrine, hydrocarbons and terpenolides. The present review is an attempt to highlight the traditional uses,pharmacognostical, phytochemical and pharmacological reports on Capparis decidua.
Keywords: Capparis decidua, Xerophytic, Caducous, Pickle.